PENDAMPINGAN PRODUKSI DAN KAMPANYE FILM PENGURANGAN RISIKO BENCANA TSUNAMI DI DESA SIDOHARJO, KABUPATEN PACITAN - Stephanus Andre Triadiputra; Agus Heru Setiawan; Sapto Hudoyo (Abdi Seni, 2019)
The geographical form of Pacitan Regency in the form of a bowl, with karst mountains that surround the city center and its outer limits directly opposite the Indian Ocean, as if it were a double-edged blade. The geographic location of Pacitan regency provides advantages such as the abundance of natural beauty that is potential to be managed as a place of tourism, but on the other hand, face to face with ocean in oceanic plate meeting with continental plate, making Pacitan regency gets threat of natural disaster in the form of earthquake and tsunami waves. The dissemination of adequate knowledge and information on the potential tsunami hazard faced by communities around Teluk Teleng as well as actions to be taken to reduce the risk of the tsunami disaster need to get serious attention and be done continuously. Production training and film campaigns with participatory methods on tsunami disaster risk reduction to communities around Teleng Bay, Sidoharjo Village, Pacitan District need to be undertaken to maintain awareness and collective awareness of the community, against tsunami hazard and as a manifestation of efforts to reduce impacts of the natural disaster.Keywords: tsunami, disaster risk reduction, film produsction, participatory.